Fine-tuning of mast cell activation by FceRIbeta chain - Ra, Chisei; Nunomura, Satoshi; Okayama, Yoshimichi (Frontiers in Immunology, 2012)
Mast cells play a key role in allergic reaction and disorders through the high affinity receptor for IgE (FcεRI) which is primarily activated by IgE and antigen complex. In humans, mast cells express two types of FcεRI on the cell surface, tetrameric αβγ2 and trimeric αγ2, whereas in mice, the tetrameric αβγ2 type is exclusively expressed. In human allergic inflammation lesions, mast cells increase in number and preferentially express the αβγ2 type FcεRI. By contrast, in the lesion of non-allergic inflammation, mast cells mainly express the αγ2type. Since the β chain amplifies the expression and signaling of FcεRI, mast cell effector functions and allergic reaction in vivo are enhanced in the presence of the β chain. In contrast, a truncated β chain-isoform (βT) inhibits FcεRI surface expression. The human FcεRIβ gene contains seven exons and a repressor element located in the forth intron, through which FcεRIβ transcription is repressed in the presence of GM-CSF. Regarding the additional signal regulatory function of the β chain, the β chain ITAM has dual (positive and negative) functions in the regulation of the mast cell activation. Namely, the FcεRIβ chain ITAM enhances the mast cell activation signal triggered by a low-intensity (weak) stimulation whereas it suppresses the signal triggered by high-intensity (strong) stimulation. In an oxazolone-induced mouse CHS model, IgE-mediated mast cell activation is required and the β chain ITAM is crucially involved. Adenosine receptor, one of the GPCRs, triggers a synergistic degranulation response with FcεRI in mast cells, for which the β chain ITAM critically plays positive role, possibly reflecting the in vivo allergic response. These regulatory functions of the FcεRIβ ITAM finely tune FcεRI-induced mast cell activation depending on the stimulation strength, enabling the FcεRIβ chain to become a potential molecular target for the development of new strategies for therapeutic interventions for allergies.